Analysis on the Socio-economic and Victimization aspect of the Victims in Nepal - Shah, Lok Bahadur; Subedee, Nutan Chandra (Journal of Advanced Academic Research, 2017)
This article is based on the study carried out in order to gauge the present scenario of crime and victimization in relation to socio-economic status of the victims. The purpose of this study was to analyze the victimization as well as socio-economic aspect of the victims of Nepal. The present scenario is that the crime and victimization are two sides of a coin and socio-economic condition of the society is one of the major factors on which it depends. The society with sound socio-economy has fewer criminal activities and fewer records of victimization. The study was based on primary data collected from the field survey. The crime victims, dependents of the victims and some key persons were the real respondents of this study. In depth interview, key informant’s interview, group discussion and published and unpublished documents were also used in this study. To make it more relevant, the data were analyzed by using interpretation, explanation and analysis. The result of the study shows that victimization mostly takes place in the society where people are long time inhabitant, uneducated, having large family size with gender discrimination as well as traditional farming and unemployment resulting in poor economic condition. Vulnerability of victims and their dependent is the outcome of their poor socio-economic status.